Measuring household resilience to food insecurity among Iranian teachers in disasters and crises - Ladaninezhad, Maryam; Mohammadi, Hamed; Esmaillzadeh, Ahmad; Pouraram, Hamed; Mohaghegh, Mostafa (Frontiers in Sustainable Food Systems, 2023)
Background Food security is susceptible to disasters and crises. Iran has frequently encountered natural disasters such as earthquakes, floods, and droughts, with a significant portion of its budget allocated to these events. While humanitarian aid and support are beneficial in critical situations, they are temporary and do not reduce vulnerability to future crises. Thus, resilience to food insecurity is a multidimensional concept that enhances the capacity to withstand future shocks and stressors. This study aimed to identify the primary dimensions of household resilience to food insecurity among teachers and characterize them across five zones in Tehran. Method We conducted a cross-sectional survey of 400 teacher households in Tehran using the Food Frequency Questionnaire (FFQ), Dietary Diversity Score (DDS), Household Food Insecurity Access Scale (HFIAS), and a resilience questionnaire. We analyzed data by using factor analysis in SPSS 16.0 according to the RIMA-I method proposed by FAO. Results The results revealed that only 45% of households across the five zones of Tehran were resilient at various levels. In Zone 1, 65% of households demonstrated resilience. The dietary diversity score was significantly higher in highly resilient households compared to vulnerable ones. Factor analysis indicated that assets were a crucial dimension of household resilience to food insecurity. A regression analysis was conducted to identify the impact of each latent variable on household resilience, revealing that dimensions such as income and food access, adaptive capacity, assets, stability, and access to essential services accounted for 56% of the resilience index. Conclusion Additional indicators are required for evaluating and enhancing resilience in food insecurity in urban areas. Consequently, policies and interventions are necessary to improve resilience to food insecurity in vulnerable households.